Depolymerization of sodium alginate in saline solutions via ultrasonic treatments: A rheological characterization. (December 2020) - Dodero, Andrea; Vicini, Silvia; Castellano, Maila
Abstract: The molecular mass of two sodium alginates with the same composition but different chain length is reduced via a simple ultrasonic treatment and monitored by rheological measurements. The polymer molecular mass decreases until a lower limiting value of 100 kg/mol is reached, with the degradation occurring via a mid-point-chain kinetic consisting into the breakage of the glycosidic bonds towards the middle of the macromolecules. The evaluation of the concentration regimes (i.e. viscosity dependence upon the polymer concentration) demonstrates that short chains are characterized by higher critical concentrations and lower scaling factors, most likely owing to their poor ability to form entanglements. Nevertheless, the typical behaviour of neutral polymer in θ solvent is observed independently of the alginate molecular mass. The viscosity temperature dependence of the investigated solutions obeys Arrhenius law in a wide temperature range. Additionally, the flow activation energy is observed to follow a linear relationship with the polymer molecular mass with values of 26.2 kJ/mol for the longest chains and 18.2 kJ/mol for the shortest ones. Consequently, ultrasonic treatment is here proved to be extremely efficient to reduce the molecular mass of alginate, thus representing a fast, safe and cost-effective approach to obtain materials with tailored properties. Graphical abstract: Image 1 Highlights: Two sodium alginates were degraded via ultrasonic treatments. Rheological measurements were used as easy tool to follow the degradation kinetic. Alginate molecular mass decreased with the ultrasonic treatment time. Chain breakage occurred via a mid-point chain model. Flow activation energy was linearly related to the polymer molecular mass.